Neonatal metabolic alkalosis and mild diuresis resulting from torasemide self-medication by the mother: a case report - Yumi Kitahiro; Mari Hashimoto; Yukako Sonda; Miki Yagi; Kotaro Itohara; Takumi Kido; Kazumichi Fujioka; Hitomi Imafuku; Tomohiro Omura; Ikuko Yano (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Torasemide, a loop diuretic, is rarely used for pregnant women because of the risk of reduced placental blood flow resulting from decreased circulating plasma volume. We experienced a case of a newborn with metabolic alkalosis and mild polyuria. The mother was suspected of self-medicating as we detected torasemide in the neonatal serum by LC-MS/MS method. Case presentation A Japanese pregnant woman in her 20s with mental illness, symptoms of panic and eating disorders, and a history of overdosing on over-the-counter medications, was referred to our hospital for birth control. She presented with vomiting following bulimia nervosa and hypokalemia. Her baby was delivered vaginally at 36 weeks and 4 days of gestation. The baby’s blood gas analysis on day 0 revealed metabolic alkalosis (pH > 7.42, HCO3 - > 28 mmHg). Up to 16 h after birth, mild polyuria and a urine output of 3.3 mL/kg/h were observed without the administration of diuretics. We suspected diuretic intake by the mother before delivery, because she had a history of taking torasemide before being referred to the hospital. As expected, torasemide was detected in the baby’s serum. The serum concentration on the first day after delivery (4.80 ng/mL) gradually decreased to 0.45 ng/mL on day 5, whereas torasemide was not detected in the maternal serum. Neonatal metabolic alkalosis improved by day 3 following birth. Conclusions This case suggests close counseling and monitoring of pregnant women before childbirth regarding their past and present use of drugs, particularly in those with mental illness.